Board Game Training: Professional Development for Facilitators at Eka Learning Center (ELC) Lhokseumawe - Mardhiah, Ainol; Lathifatuddini, Lathifatuddini; Hayati, Ulfi; Muna, Hayatul (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2025)
Eka Learning Center (ELC), a non-formal education institution in Lhokseumawe, Aceh, faces challenges in maintaining student focus and engagement. To address this, a training program was conducted to equip facilitators with the skills to use board games as interactive learning tools. The program consisted of needs analysis, training in board game creation, implementation mentoring, and evaluation. Findings indicate that the use of board games significantly enhances student focus and engagement, creating a more interactive and stimulating learning environment. Facilitators also improved their competencies in innovative teaching methods. The developed board game is currently being prepared for intellectual property registration, reflecting its potential for broader application. This initiative not only strengthens the learning experience at ELC but also promotes innovation in non-formal education, contributing to the advancement of local educational practices.